Leading the consumer by the nose: on the commercialization of olfactory design for the food and beverage sector. Issue 1 (December 2015) - Spence, Charles
Abstract Many researchers distinguish between two senses of smell—orthonasal (when we inhale or sniff) and retronasal (when volatiles are pulsed out from the back of the nose during eating). Orthonasal olfactory cues are key to setting our expectations concerning the sensory and hedonic attributes of food and drink; by contrast, retronasal olfactory cues are central to the experience of taste (or, better said, flavour). Food and beverage providers are increasingly modifying the product-extrinsic olfactory cues associated with their offerings in order to try and influence our food behaviours and hopefully enhance our multisensory product experiences. One way in which this is happening is via the introduction of olfactorily enhanced product packaging into the marketplace. A second key route is via the control and modification of the olfactory 'smellscape' in and around chain restaurants and food/beverage outlets. A third route that is slowly starting to emerge is technology-enabled olfactory marketing via scent-emitting billboards and scent-enabled plug-ins for mobile devices. Key opportunities and concerns, ethical and otherwise, surrounding the recent growth of olfactory marketing (specifically those examples incorporating food aromas) are highlighted. Ultimately, the question that we should all perhaps be asking ourselves is whether we are all being 'led by the nose', knowingly or otherwise, into unhealthy food behaviours.